Improving Brand Awareness and Market Competitiveness in Homecare Services: Business Strategy Analysis of Care Your Self (CYS) - Nanda, Yumas Gia; Astuti, Novika Candra; Uno, Indra Cahya (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
The homecare healthcare industry in Indonesia is experiencing rapid growth due to the aging population, increasing prevalence of chronic diseases, and rising demand for personalized healthcare services. Despite this opportunity, many providers face challenges in building market visibility and competing in a fragmented and price-sensitive market. This paper analyzes the business strategy of Care Your Self (CYS), a comprehensive homecare nursing service provider, focusing on brand awareness and competitive positioning. Using a mixed-method approach and strategic analysis frameworks such as SWOT, PESTLE, Porter’s Five Forces, EFAS-IFAS, and AHP, this study proposes actionable strategies to improve CYS's brand strength and market competitiveness. Results show that a combination of digital marketing, service differentiation, IT infrastructure development, and strategic partnerships is essential for enhancing public awareness and driving sustainable business growth. The findings contribute to the broader understanding of healthcare marketing and strategic planning for emerging health service providers in developing economies.